2022
DOI: 10.1039/d1ay02176a
|View full text |Cite
|
Sign up to set email alerts
|

A phenazine-imidazole based ratiometric fluorescent probe for Cd2+ ions and its application in in vivo imaging

Abstract: A new phenazine-imidazole based Schiff base (PIS) fluorescent probe have been developed for the ratiometric detection of Cd2+ ion in aqueous media at physiological pH. PIS upon binding with Cd2+...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In Figure 7, PIS was developed as a novel ratiometric phenazine-imidazole-Schiff base fluorescent probe [76].…”
Section: Fluorescent Probes To Detect CD 3+mentioning
confidence: 99%
“…In Figure 7, PIS was developed as a novel ratiometric phenazine-imidazole-Schiff base fluorescent probe [76].…”
Section: Fluorescent Probes To Detect CD 3+mentioning
confidence: 99%
“…49 A phenazine-imidazole based ratiometric fluorescent probe was designed by Wang et al to recognise Cd 2+ ions only in 2022, which showed a limit of detection value of 2.10 × 10 −8 (M). 50 Although Schiff bases containing N, O, S donors binding with Cd 2+ with 2 : 1 stoichiometry are less known, Rajesh et al in 2021 published a work on a quinoline based Schiff base for detecting cadmium in semi aqueous medium with 2 : 1 stoichiometry and a LOD value of 14.8 nM. 51 Now in this present work, we have successfully designed and fabricated a simple, cost-effective biphenyl thiosemicarbazide based fluorescent “turn-on” reversible chemosensor which detects Cd 2+ with a detection limit of (1.59 ± 0.054) × 10 −8 (M), which is a pretty good value compared to many previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…Among these heavy metal ions, cadmium ions are highly toxic to human beings and lead to serious damage to the nervous system, kidney and liver, causing metabolic disorders and other related diseases 4‐6 . Cd 2+ is a priority pollutant and tolerable Cd 2+ concentrations in water are limited as 27 nmol L −1 due to the strong toxic role of cadmium ions 7,8 . However, cadmium ions may be discarded to environments with living organisms from fossil fuel combustion, phosphate fertilizer and battery industries 9‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Cd 2+ is a priority pollutant and tolerable Cd 2+ concentrations in water are limited as 27 nmol L −1 due to the strong toxic role of cadmium ions. 7,8 However, cadmium ions may be discarded to environments with living organisms from fossil fuel combustion, phosphate fertilizer and battery industries. [9][10][11] Therefore, it is urgent and essential to develop a sensitive and rapid method for monitoring Cd 2+ levels in water environments and biological systems.…”
Section: Introductionmentioning
confidence: 99%